RETRACTED: Nanoformulated Ajwa (Phoenix Dactylifera) Bioactive Compounds Improve the Safety of Doxorubicin without Compromising Its Anticancer Efficacy in Breast Cancer - Kavitha Godugu; Ali H. El-Far; Soad Al Jaouni; Shaker A. Mousa (Molecules)
One of the major causes of women’s death in the world is breast cancer. Consequently, numerous regimens for the control of this severe disease have been created. The chemotherapeutic agent doxorubicin (DOX) is frequently used to treat breast cancer, but DOX can also cause cardiotoxic effects that lead to heart failure. Therefore, many research studies have been done to find a natural product that effectively potentiates or does not interfere with DOX’s anticancer effect and protects against its cardiotoxicity. We studied the impact of combined nanoformulated Ajwa (Phoenix dactylifera) selected bioactive compounds (BAC) rutin (R) and quercetin (Q) in nude mice breast cancer xenografts on DOX-mediated anticancer efficacy. We also studied if this Ajwa BAC could safeguard against DOX-mediated cardiomyopathies by evaluating plasma cardiac troponin-I (cTn-I) levels and cardiac histopathology. Nanoformulated Ajwa BAC effectively alleviated weight loss induced by DOX in mice and significantly decreased the elevated cTn-I. Furthermore, 5 mg RQ-NPs/kg of nude mice that subcutaneously daily injected for 11 days, attenuated the histopathological alterations induced in cardiac muscles due to DOX without any interference with the anticancer effects of DOX against breast cancer.